2019
DOI: 10.1159/000502328
|View full text |Cite
|
Sign up to set email alerts
|

Association between Aortic Calcification, Cardiovascular Events, and Mortality in Kidney and Pancreas-Kidney Transplant Recipients

Abstract: word count: 246 16 Word count: 3110 Abstract 34 Background: Cardiovascular (CV) disease is the leading cause of death in kidney and 35 simultaneous pancreas-kidney (SPK) transplant recipients. Assessing abdominal aortic 36 calcification (AAC), using lateral spine x-rays and the Kaupilla 24-point AAC (0-24) score, 37 may identify transplant recipients at higher CV risk. 38 Methods: Between the years 2000-2015, 413 kidney and 213 SPK first transplant recipients 39 were scored for AAC at time of transplant and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The literature on abdominal aorta calcification (AAC) assessment by plain pelvic X-ray or dual X-ray absorptiometry, using visual grading scales, is more extensive [13]. Studies evaluating this method showed results similar to our findings, with significant associations of a high-AAC with all-cause mortality and cardiovascular events in multivariable Cox regression analyses [12,20,21]. Timing of the imaging procedure in previous studies is an important difference compared with the current study, as imaging procedures were performed after transplantation and at the physician's discretion, instead of CT procedures during the screening prior to transplantation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The literature on abdominal aorta calcification (AAC) assessment by plain pelvic X-ray or dual X-ray absorptiometry, using visual grading scales, is more extensive [13]. Studies evaluating this method showed results similar to our findings, with significant associations of a high-AAC with all-cause mortality and cardiovascular events in multivariable Cox regression analyses [12,20,21]. Timing of the imaging procedure in previous studies is an important difference compared with the current study, as imaging procedures were performed after transplantation and at the physician's discretion, instead of CT procedures during the screening prior to transplantation.…”
Section: Discussionsupporting
confidence: 81%
“…CAC, expressed as Agatston score by non-contrast enhanced cardiac computed tomography (CT), demonstrated progression within four years in prevalent kidney transplant recipients and is associated with myocardial infarction and mortality [14][15][16][17][18]. Aorto-iliac calcification, by plain pelvic X-ray, dual X-ray absorptiometry, or semi-quantitative CT assessment, was associated with inferior overall patient survival [12,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing AAC score, especially score values greater than 8-15, has been associated with severely increased risk for CV events in dialysis patients [29][30][31]. AAC score 8 has been used as a cut-off value for high calcification in transplant patients [32,33]. Lewis et al showed, that there is a continuous 7-8% increase in risk of CV events for each 1 point increase in AAC score without an exact cut-off point [33].…”
Section: Discussionmentioning
confidence: 99%
“…AAC score 8 has been used as a cut-off value for high calcification in transplant patients [32,33]. Lewis et al showed, that there is a continuous 7-8% increase in risk of CV events for each 1 point increase in AAC score without an exact cut-off point [33]. Based on these previous studies, AAC-score 0 in 13/17 patients and the highest AAC score 8/24 in our study should indicate mild to moderate CV risk.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiovascular complications are the main causes of mortality in patients with CKD. Vascular calcification is also associated with a higher mortality risk in CKD patients following kidney transplantation, and may be a predictor of poor graft outcomes 7 . As existing treatments for vascular calcification in CKD patients are limited, there is an urgent need to identify new therapeutic targets for this disease.…”
Section: Introductionmentioning
confidence: 99%